2019
DOI: 10.33737/gpps19-bj-008
|View full text |Cite
|
Sign up to set email alerts
|

Shock–Vortex Interaction in a Transonic Turbine Cascade

Abstract: In this paper, we have investigated numerically the interaction between secondary flow and a normal compression shock in a transonic turbine cascade. We observe that the sudden deceleration caused by the compression shock triggers an instability in weaker regions of the vortex system. This instability forms a pattern of concentric rings of elevated vorticity, which, in turn, cause the shock to deform into the same concentric wave-like pattern. The same pattern appears in the entropy distribution just downstrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Given the complex flow conditions at the trailing edge caused by unsteady trailing edge vortex shedding and subsequent interaction with shock structures this is difficult to predict computationally. 7 Supercritical loading is the fourth and final stage, with the trailing edge pressure surface shock completely departing the base pressure region and the flow within the passage becoming completely choked.
Figure 1.Stages to limit loading: Terminology.
…”
Section: Introductionmentioning
confidence: 99%
“…Given the complex flow conditions at the trailing edge caused by unsteady trailing edge vortex shedding and subsequent interaction with shock structures this is difficult to predict computationally. 7 Supercritical loading is the fourth and final stage, with the trailing edge pressure surface shock completely departing the base pressure region and the flow within the passage becoming completely choked.
Figure 1.Stages to limit loading: Terminology.
…”
Section: Introductionmentioning
confidence: 99%
“…The approach shown here is used to assess shock-wave vortex interaction in Mimic et al (2019) where it is found to produce similarly satisfactory results.…”
Section: Loss Analysismentioning
confidence: 94%